Marketing y el incremento de las ventas en el centro comercial “La Bahía” de la ciudad de Babahoyo - Cunalata Ramirez, María Angélica (2017)
At present, the big companies are oriented to the satisfaction of the customer, for that they use a lot of marketing and their strategies. By means of these tends to establish which is the specific market and is oriented to all in the organization to have loyal customers, it is for this reason that establishing strong relationships with customers is very important, and must be based on real and lasting value